Packaging Implications for Wine and Alcoholic Beverages : FSHN24-3/FS458, 9/2024 - Wendrick, Nicholas; Budner, Drew; MacIntosh, Andrew J.; Thompson-Witrick, Katherine A. (EDIS, 2024)
This is a review of the most commonly available wine packaging types currently on the market. This includes glasses bottles, polethylene terephthalate bottles (PET), bag-in-box (BIB), aluminum cans, and Tetra Pack. This review focuses on the pros and cons of each packaging type in relation to wine and alcoholic beverages.